The role of mitochondria in autism: an analysis of mitochondrial dysfunction in ASD - Van Der Colff, Rachelle (Department of Molecular and Cell Biology, 2026)
Autism is a neurodevelopmental disorder characterised by challenges in socio-communication, restricted and repetitive behaviours and interests. Despite the 1 in 59 prevalence of ASD (Autism Spectrum Disorder), it is severely understudied in minority populations, such as the Sub-Saharan population. This is mainly because of a lack of genetic biobanks, meaning African researchers cannot compete with the large-scale studies of the Northern Hemisphere. The researchers involved in this project have previously set up a unique cohort of age-matched South African children with and without ASD. As epigenetics is becoming increasingly more popular in studying neuro-disorders, this research team has investigated the differential methylation (DM) patterns associated with ASD using a 450K array, and found several DM genes associated with mitochondrial metabolism. Hence the investigation into (and the title of this thesis) the association of mitochondrial dysfunction to ASD. This thesis aims to validate the differential methylation of a subset of these genes, to investigate STOML2 expression levels in ASD as a gene critical to mitochondrial fusion. Using different qPCR techniques, the relative mitochondrial copy number between ASD and neurotypical children was also analysed, looking at both copy number variation, and copy number deletion. This research successfully validated the DM of selected genes using two methods of validation, and identified both PCCB and PCDHA12 as significantly hypomethylated in children with ASD. A clear increase in mitochondrial copy number was also observed between ASD and neurotypical children. While mitochondrial deletions were not observed, this was to be expected because none of the ASD children in the cohort has any diagnosis of a severe mitochondrial disease (which would be clear phenotype of mitochondrial deletions). In conclusion, this thesis reinforces the role of mitochondria and its dysfunction in ASD.